2022
DOI: 10.3390/genes13050759
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of BMPR2 mRNA Expression in Peripheral Blood of Pulmonary Arterial Hypertension Patients: A Marker for Disease Severity?

Abstract: Pulmonary arterial hypertension (PAH) can be caused by pathogenic variants in the gene bone morphogenetic protein receptor 2 (BMPR2). While BMPR2 protein expression levels are known to be reduced in the lung tissue of heritable PAH (HPAH) patients, a systematic study evaluating expression in more easily accessible blood samples and its clinical relevance is lacking. Thus, we analyzed the BMPR2 mRNA expression in idiopathic/HPAH patients and healthy controls in blood by quantitative polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…For this study 79 patients with an invasively confirmed diagnosis of IPAH or HPAH and 30 healthy controls were prospectively recruited between May 2019 and January 2020. 12 All patients received an extended iron status assessment in addition to the routine diagnostic testing. The BMPR2 expression analysis and the cohort's clinical characteristics were described previously.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this study 79 patients with an invasively confirmed diagnosis of IPAH or HPAH and 30 healthy controls were prospectively recruited between May 2019 and January 2020. 12 All patients received an extended iron status assessment in addition to the routine diagnostic testing. The BMPR2 expression analysis and the cohort's clinical characteristics were described previously.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, only BMPR2 mRNA in whole blood but not protein levels in serum were statistically significant reduced in mutation-carriers versus BMPR2 noncarriers. 12 Similar to the BMP ligands, inflammatory markers, such as IL6-levels or the C-reactive protein or the hypoxia-indicating marker erythropoietin did not correlate with serum hepcidin levels. By contrast, a strong positive correlation was observed in patients between serum hepcidin and ferritin (Pearson's correlation: 0.777, p < 0.0001; Figure 3), and a negative correlation with transferrin (p = 0.005), soluble transferrin receptor (p = 0.038), ferritin index (p = 0.002), and erythrocyte count (0.030) (Table 3).…”
Section: Hepcidin Levels and Pathway Related Parametersmentioning
confidence: 89%
See 3 more Smart Citations